2010
DOI: 10.1097/ijg.0b013e3181a2fa31
|View full text |Cite
|
Sign up to set email alerts
|

Goniotomy for Juvenile Open-Angle Glaucoma

Abstract: Goniotomy is a potentially effective initial surgical treatment of JOAG. Goniotomy for JOAG can be successfully performed using a standard goniotomy technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Studies have shown that viscocanalostomy, goniotomy and external trabeculotomy can also be performed in eyes with juvenile-onset open angle glaucoma [20,21,22]. However, these studies have small numbers, are mostly retrospective and do not take into account the long-term structural and functional changes associated with IOP control in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that viscocanalostomy, goniotomy and external trabeculotomy can also be performed in eyes with juvenile-onset open angle glaucoma [20,21,22]. However, these studies have small numbers, are mostly retrospective and do not take into account the long-term structural and functional changes associated with IOP control in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, ab externo trabeculectomy is not recommended as a first-line treatment for JOAG despite the potential for greater IOP reduction [2,7]. Rather, angle-based procedures are preferred as they spare the conjunctiva and avoid the potential of life-long bleb-related complications [2,7,8]. As bleb morphology is critical to ocular health, the potential for long-term bleb-related complications should be emphasized when discussing surgical options with these young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Arora et al [ 7 ] observed mean reductions of 10 mm Hg in IOP and 0.7 medications 12 months after ab interno trabeculectomy with the trabectome (NeoMedix Corp., Tustin, CA). Moreover, Yeung and Walton [ 2 ] observed a comparative 12.7 mm Hg reduction in IOP after goniotomy. IOP has also been shown to be reduced by 12.5–16 mm Hg following gonioscopy-assisted transluminal trabeculotomy, with reductions in medications ranging from 1.3–1.74 [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of goniotomy over many other glaucoma surgical procedures is that it spares the conjunctiva, thus preserving un-operated conjunctiva for future surgical procedures. Although goniotomy is not a typical choice for aphakic glaucoma or open-angle juvenile glaucoma, some authors suggest its use for these diagnoses [ 25 , 26 ]. In addition, it has also been suggested that there may be a role for prophylactic goniotomy in selected aniridia patients without glaucoma [ 27 ].…”
Section: Surgical Optionsmentioning
confidence: 99%